2018
DOI: 10.1002/bmc.4325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of terizidone in plasma using HPLC‐UV method and its application in a pharmacokinetic study of patients with drug‐resistant tuberculosis

Abstract: A chromatographic method has been developed and validated for the first time for analysis of terizidone in plasma. Terizidone was extracted from plasma by protein precipitation using a mixture of acetonitrile and methanol (1:1, v/v). The chromatographic separation was achieved with a gradient of acetonitrile and water both containing 0.1% formic acid on a Supelco Discovery HS C (150 × 4.6 mm, 5 μm) reversed-phase column. Propranolol was used as the internal standard. The total run-time was 18 min. The calibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The lower limit of quantification was 3.125 µg/mL, while the limit of detection was 0.78 µg/mL. The coefficient of determination value ranged between 0.9988 and 0.9999, and calibration curves were linear [21].…”
Section: Methodsmentioning
confidence: 99%
“…The lower limit of quantification was 3.125 µg/mL, while the limit of detection was 0.78 µg/mL. The coefficient of determination value ranged between 0.9988 and 0.9999, and calibration curves were linear [21].…”
Section: Methodsmentioning
confidence: 99%
“…Calibration curves were linear with coefficient of determination ranging between 0.9988 and 0.9999. The lower limit of quantification and limit of detection was 3.125 and 0.78 μg mL −1 , respectively . Cycloserine concentrations were analysed using ultra‐performance liquid chromatography–tandem mass spectrometry method and validated according to the international guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…The extensive literature survey shows several reported methods which are; UV method [4], HPLC method for TRZ in plasma [5], stability study for TRZ [6] (degradation products were not separated nor reported), the two degradation products of TRZ are reported by HPTLC and MS/MS method [7] (the DPs are marked with an asterisk in paper and cited which are reported in literature), HPTLC and LC/MS/MS methods are reported [8]. None of the reported literature investigates the entire impurity profile for TRZ, therefore it was an opportunity and challenge to study stress degradation and report the impurity profile of TRZ.…”
Section: Fig 1: Chemical Structure Of Terizidonementioning
confidence: 99%